Effect of the incorporation of polysaccharide from Falkenbergia rufolanosa on beef sausages for quality and shelf life improvement. (May 2021) - Feki, Amal; Sellem, Imen; Hamzaoui, Asma; Ben Amar, Wiem; Mellouli, Lotfi; Zariat, Ahmed; Nasri, Moncef; Ben Amara, Ibtissem
Abstract: This study was undertaken to isolate a sulfated polysaccharide from red macro alga Falkenbergia rufolanosa (FRP) and to evaluate its potential effect as antioxidant additive in beef sausages formulation. The antioxidant, functional and hemolytic activities were studied. Data revealed that this polymer has an important antioxidant activities (up to 87% for metal chelating assay) and emulsion stabilizing capacities. The addition of FRP into sausages stored at 4 °C for 12 days induced depletion in lipid oxidation, in myoglobin oxidation and in free fatty acids contents up to 3.33 mg equivalent MDA Kg −1 Sausages, 28.28% and 2.35%, respectively, while, an improvement in the transformation of the Heme iron was noted, compared with the standard formulation. A significant stability in the color parameters (L*, a* and b* values) with a marked decrease in the microbial counts were as well noticed. Interestingly, a significant progression in the textural parameters of samples containing FRP was observed as well as higher sensory scores by panelists. According to sensorial evaluations, this polymer improved the consumer acceptability and preference. In conclusion, our findings provided evidence that FRP could be used as a potent natural additive and could replace synthetic antioxidant compound in food industry. Highlights: Polysaccharide (FRP) was extracted from red marine alga Falkenbergia rufolanosa . FRP exhibited potent functional and antioxidant activities. FRP was added as antioxidant food additive in the formulation of beef sausages. FRP inhibited the lipid oxidation of beef sausages during refrigerated storage. FRP improved the quality of beef sausages conserved at 4 °C for 12 days.